Functional symptoms in dermatology: Part 1. (27th August 2019) - Ball, S. L.; Howes, C.; Affleck, A. G.
Abstract: Functional – or somatoform – symptoms are those that arise with no proven organic pathology. Also known as 'medically unexplained' symptoms, they can present in any medical speciality, including dermatology. Mucocutaneous pain syndromes and functional pruritus are two examples of functional disorders encountered by dermatologists. Patients presenting with somatoform symptoms have paradoxically complex and often subjectively severe symptomatology, yet minimal abnormalities on clinical examination or investigation. Such disparity can be frustrating and distressing for patients and clinicians alike, and there are many pitfalls regarding overinvestigation and misleading communication. However, with an honest and open approach – sometimes requiring collaboration with psychological services – management of functional symptoms can be effective, and patients can be successfully rehabilitated. Abstract : Click here for the corresponding questions to this CME article.